A Parametric Study of Laser-Directed Energy Deposited DSS 2205: Microstructure and Mechanical Properties Perspectives - Mahey, Vishal; Johnson, Grant A.; Burad, Prayag; Gonzalez-Ojeda, Roberto; Quintana, Maria J.; Collins, Peter C.; Roy, Sougata (Springer Science and Business Media LLC, 2025)
Duplex stainless steels (DSS) are corrosion-resistant materials with excellent mechanical properties. This family of steels is only a recent addition to the additive manufacturing (AM) realm due to the limited availability of DSS powder in the past. This study has investigated the effect of varying energy flux (laser power and scanning speed) in a laser-based directed energy deposition AM process on the as-deposited materials state of DSS 2205, a material widely used in marine applications. The primary focus was to understand how changes in laser power (200 W and 300 W) and scanning speed (10 mm/s and 15 mm/s) influence key microstructural features such as phase distribution (δ-ferrite and γ-austenite), grain size, morphology, defects, and microhardness of the as-deposited material. Microstructural analysis revealed a significant correlation between the processing parameters and the resulting microstructure. Increasing the scanning speed reduces the defect content in the samples, while increasing laser power results in larger δ-ferrite grains. The hardness was influenced by both the γ-austenite content and the δ-ferrite grain size. This study provides a pathway for tailoring directed energy deposition (DED) conditions to achieve high-quality and dimensionally accurate components, particularly suited for demanding marine applications. ©The authors ©Springer ©JOM.
Keywords: Compressive strength; Corrosion resistance; Duplex stainless steel; Hard facing; Laser materials processing; Microhardness; Steel corrosion